(untitled) (TAJ: Journal of Teachers Association, 2018)
Psoriasis is a common, chronic and recurrent inflammatory disease of the skin. Clinically, disease can present with cutaneous and nail lesions. Both fingernails and toenails may be affected. The present study was conducted to study the abnormal nail changes in patients with psoriasis and to find correlation between nail changes and some clinical parameters. The study was undertaken in Skin & VD outpatient department of Rajshahi Medical College Hospital, Rajshahi. One hundred patients of psoriasis of all age and both sexes were enrolled for studying the nail changes, in whom diagnosis of psoriasis was made clinically. In any case of abnormalities clinically suspected of fungal infection, further mycological investigations were performed. Nail changes were present in 60 patients (60%, P<0.05) with psoriasis. Pitting was the most common finding on fingernails (70%), followed by onycholysis (35%). Subungual hyperkeratosis was the most common finding in toenails (34.37%). A very strong association was seen between nail changes and joint pain. There was positive correlation between nail abnormalities and duration of psoriasis. Nail involvement is common in patients with psoriasis. Pitting, onycholysis, subungual hyperkeratosis are the most frequent nail changes in psoriatic patients. TAJ 2016; 29(1): 29-32